FRI0103 Erythrocyte Methotrexate Polyglutamate Levels Do Not Determine Efficacy and Tolerability of Methotrexate in Rheumatoid Arthritis. (15th July 2016) - Dhir, V.; Sandhu, A.; Bhatnagar, A.; Dhawan, V.; Kaur, J.; Sood, A.; Sharma, A.; Sharma, S.
Abstract : Background: Methotrexate (MTX), a mono-glutamate, by addition of 2–6 more glutamate moieties, is converted to methotrexate polyglutamates (MTX PGs) intracellularly. These are the active compounds mediating folate pathway inhibition and increase in adenosine. Erythrocyte polyglutamate levels (RBC MTX PGs) are surrogate markers for levels inside lymphocytes and hepatocytes.Variability in RBC MTX PGs formed intracellularly (despite similar MTX dose) may be one of the factors determining variability in efficacy of MTX. Previously, contrasting results have been found on their association with efficacy and few prospective studies exist. Objectives: To assay levels of erythrocyte methotrexate polyglutamate (1–5) levels in patients with rheumatoid arthritis and assess their relationship to efficacy and adverse effects. Methods: Prospective study that included patients of RA (fulfilling 1987 ACR), aged 18–65 years with active disease (DAS28–3v>3.2) and not on methotrexate. Oral MTX was started at 15 mg/week and increased to 25 mg/week at 8 weeks. Disease activity measured using DAS28 (3 variables), and at 24 weeks patients classified into responders (EULAR good or moderate response) or non-responders. MTX-PG levels (PGs 1–5) assayed in deproteinised packed RBCs by HPLC using reverse phase (C18 column) and post-column derivitization using UV photo-oxidation followed by fluorescent detection (ex 274; em 470 nm). Results: Included 117 patients, with mean (±SD) age of 42.7±11.9 years, disease duration 2.0±1.7 years, 71.8% RF+ and 85.7% CCP+. At 24 weeks, there were 57 responders and 33 non-responders with no significant difference in mean (±SD) MTX dose (21.7±3.9, 22.7± 4.1mg/week, p=ns), age, disease duration, but with lower BMI (21.7±3.9, 24±4.5 kg/m 2, p=0.02) and higher baseline DAS28(3) (6.5±0.7, 6.1±0.9, p=0.02). There was an early and sustained gap between the curves of DAS28(3) between responders and non-responders (Figure, left upper quadrant). Methotrexate PG levels increased till 24 weeks (mainly PG3 and PG4), with reasonable correlation between dose and MTX PG levels (r=0.38, p<0.05). There was no significant difference in the mean methotrexate polyglutamate levels (sum of pgs 1–5) nor individual PGs between responders and non-responders at any of the visits (4, 8, 16 and 24 weeks) ((Figure, right upper quadrant and lower panel). Symptomatic adverse effects occurred in 34 patients (57 episodes) – most commonly nausea. There was no significant difference in MTX-PG levels between patients with and without symptomatic adverse effects. Mild transaminitis occurred in 43 patients (at atleast one visit) and mild thrombocytopenia in 16 patients; with no difference in methotrexate polyglutamate levels. Conclusions: Our study suggests that MTX-PG levels is not a determinant for response to MTX or their adverse effects. This is different from a previous prospective study, we think the differnce lies in MTX dose and clear classification as reponder and non-responders in our study. Disclosure of Interest: None declared